2017
DOI: 10.1016/j.chom.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Live Attenuated Influenza Vaccine that Elicits Broad Protection in Mice and Ferrets

Abstract: New influenza vaccines that provide effective and broad protection are desperately needed. Live attenuated viruses are attractive vaccine candidates because they can elicit both humoral and cellular immune responses. However, recent formulations of live attenuated influenza vaccines (LAIVs) have not been protective. We combined high-coverage transposon mutagenesis of influenza virus with a rapid high-throughput screening for attenuation to generate W7-791, a live attenuated mutant virus strain. W7-791 produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…However, it was reported that non-specific immunity against non-influenza respiratory viruses in children vaccinated with a live-attenuated influenza vaccine (LAIV) was short-lived with the duration of as long as 1−2 weeks ( 62 ). Furthermore, many animal studies on cross-protection by LAIVs have presented protection data by performing in vivo challenge at 2−4 weeks after the vaccination ( 11 , 17 , 33 , 63 , 64 ). Considering these observations, our experimental design of the challenge at 5 weeks days after the boosting vaccination cannot be explained by non-specific mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported that non-specific immunity against non-influenza respiratory viruses in children vaccinated with a live-attenuated influenza vaccine (LAIV) was short-lived with the duration of as long as 1−2 weeks ( 62 ). Furthermore, many animal studies on cross-protection by LAIVs have presented protection data by performing in vivo challenge at 2−4 weeks after the vaccination ( 11 , 17 , 33 , 63 , 64 ). Considering these observations, our experimental design of the challenge at 5 weeks days after the boosting vaccination cannot be explained by non-specific mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CAIVs have many immunological advantages in terms of cross-protection over the other vaccine platforms, including the delivery of a whole set of antigens, the induction of mucosal IgA antibodies, and T-cell responses, as well as the stimulation of innate immunity ( 12 15 ). Perhaps most importantly, it has been widely acknowledged that T-cell immunity, which targets viral proteins that are relatively conserved between different influenza strains, is the key to the cross-protection by natural infection or vaccination ( 16 , 17 ). Therefore, if all of these factors are combined properly and reinforced by a rational vaccination strategy, a CAIV is expected to serve as a powerful platform for a universal influenza vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…While highly successful, this method can present disadvantages, such as labor intensiveness, the difficulty in assessing multifunctional proteins, and a lack of insight into intergenic regions. We therefore chose to use a method that has proven successful in the study of other viral (17)(18)(19) and bacterial (20,21) genomes. We created an HSV-1 mutant library by random insertion of a disruptive 1.2-kbp transposon across the viral genome.…”
Section: Importancementioning
confidence: 99%
“…There are global efforts to increase the breadth of protection of influenza vaccines, with an eventual goal of universal protection (reviewed in), and most strategies have been evaluated in ferret models. A non‐exhaustive list of strategies to induce heterosubtypic immunity against influenza evaluated in ferrets include: HA stem vaccination; prime‐boost with chimeric HA‐based vaccines; use of conserved influenza proteins such as nucleoprotein (NP), matrix‐1 (M1), matrix‐2 (M2) and RNA polymerase subunit B1 (PB1); replication‐deficient viruses; live attenuated formulations; the use of potent adjuvants such as Protollin, glucopyranosyl lipid adjuvant—aqueous formulation (GLA‐AF), CoVaccine HT, cationic adjuvant formulation and poly‐g‐glutamic/chitosan nanogel; Escherichia coli ‐derived vaccines; DNA, mRNA and viral vector vaccines; and the use of virus‐like particles (VLP) . Additional examples of important ferret studies include (but are not limited to) evaluating the influence of changing the route of influenza inoculation on subsequent immunity and the use of neuraminidase (NA) inhibitors as prophylaxis …”
Section: Ferrets For Influenza Surveillance and Vaccine Developmentmentioning
confidence: 99%